A Cross-sectional Study on Patients’ Satisfaction with Dietary Services in a Tertiary Care Hospital of Malwa Region, Punjab - Shamsher Singh; Paresh Prajapati (Journal of Integrated Health Sciences)
Introduction: The quality and quantity of the food served by the hospital have an impact on the treatment and quick recovery of patients. Moreover, dietary service is a significant factor in patient satisfaction. With the importance of hospital diet in patients’ satisfaction and its link to clinical outcomes in mind, this study was conducted to assess the patient satisfaction with Adesh Hospital’s dietary services. Aims: (1) To measure the proportion of inpatients who were satisfied with dietary services, (2) To assess the quantity and hygiene of food as perceived by patients, (3) To evaluate the comparison between sociodemographic factors, type of ward, and patients’ satisfaction toward dietary services. Materials and Methods: A hospital-based cross-sectional study was conducted in a tertiary care hospital located in Bathinda, Punjab, among 210 patients, using the convenience sampling technique. A questionnaire was developed and pilot-tested based on the objectives of the study. Results: When the various aspects of patient satisfaction with dietary services were examined, the study revealed that 85.24% of patients were overall satisfied with dietary services. Data analysis showed that male patients were significantly more satisfied than females (P < 0.05), and the difference between satisfaction level among rural and urban patients was not significant (P > 0.05). Conclusions: Based on the findings, it could be concluded that overall satisfaction with the hospital’s dietary services was very high. Most of the participants reported that food was always served on time, and all agreed that it was cooked appropriately. Nearly three-fourths of the participants rated the taste of the food as excellent, and all described the staff’s behavior as friendly. To further enhance quality, regular feedback mechanisms and periodic reviews can be implemented to sustain excellence and identify areas for continuous improvement.